Corrosion inhibition properties of pyrazolylindolenine compounds on copper surface in acidic media - Ebadi, M.; Ali, H.M.; Khaledi, H.; Basirun, Wan Jefrey (2012)
Background: The corrosion inhibition performance of pyrazolylindolenine compounds, namely 4-(3,3-dimethyl-3H-indol-2-yl)-pyrazole-1-carbothioamide (InPzTAm), 4-(3,3-dimethyl-3H-indol-2-yl)-1H-pyrazole-1-carbothiohydrazide (InPzTH) and 3,3-dimethyl-2-(1-phenyl-1H-pyrazol-4-yl)-3H-indole (InPzPh),) on copper in 1M HCl solution is investigated by electrochemical impedance spectroscopy (EIS), open circuit potential (OCP) and linear scan voltammetry (LSV) techniques. Results: The results show that the corrosion rate of copper is diminished by the compounds with the inhibition strength in the order of: InPzTAm[modifier letter right arrowhead] InPzTH [modifier letter right arrowhead] InPzPh. The corrosion inhibition efficiencies for the three inhibitors are 94.0, 91.4 and 79.3, for InPzTAm, InPzTH and InPzPh respectively with the same inhibitor concentration (2 mM). Conclusion: From the EIS, OCP and LSV results it was concluded that pyrazolylindolenine compounds with S-atom (with an amine group) have illustrated better corrosion inhibition performance compared to hydrazine and phenyl group.